Penilaian Kondisi Permukaan Jalan Menggunakan Aplikasi Roadroid pada Jalan Veteran - Bandung Kota Malang - Marjono Marjono; Burhamtoro Burhamtoro; Rinto Sasongko (Kadiri University, 2022)
Roads are the most important infrastructure in supporting community activities. Damage that occurs to the road surface can cause congestion, inconvenience, and even accidents. One of the roads that was damaged was Veteran Street to Bandung City Malang Street. The purpose of this research is to evaluate the condition of the road surface and determine the appropriate repair efforts. The research was conducted by conducting a direct survey using the Roadroid application. The data obtained is in the form of eIRI, cIRI, vehicle speed, object position, distance from the initial position and temperature. Furthermore, an analysis of Remaining Structural Life and Road Condition Index was carried out. From this analysis can be used to determine the right improvement efforts. The results showed that the road conditions after being repaired by patching were still in poor condition with a percentage of poor road conditions of 65.43%. For this reason, it is necessary to carry out repair efforts by re-coating with a minimum thickness of 40 mm, for the type of LTBA-A material at a cost per ton of Rp. 1,106,723. The results of this study can be used as a reference and reference in efforts to repair roads and can be used as a database for road conditions for city governments.